PENGARUH PENERAPAN SISTEM MONITORING PELAPORAN PEMBAYARAN PAJAK (MP3), PENGETAHUAN TENTANG KORUPSI, DAN KEADILAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA PEKANBARU TAMPAN - Fariz Hermawan; Zirman Zirman; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to find out whether Implementation of MP3’s system, knowledge of corruptions and fairness of taxation to compliance of individual taxpayers in Pekanbaru Tampan Tax Authority. The applied statistic test was multiple linier regressions. Data is primary and obtained through questionnaire. There are 70 questionnaire whichcan be analyze. Respondent are come from individual taxpayers who use tax payment reporting monitoring system(MP3). The result of this research consistent of: Implementation of MP3’s system (X1), knowledge of corruptions(X2), fairness of taxation (X3) and taxpayer compliance (Y). The result of this research show that Implementation of MP3’s system have a significant influence to compliance of individual taxpayers, knowledge of corruptions have a significant influence to compliance of individual taxpayers and fairness of taxation have a significant influence to compliance of individual taxpayers.Keywords: MP3’s system, knowledge of corruptions, fairness of taxation, taxpayer compliance, compliance of individual taxpayers